2015
DOI: 10.1155/2015/751738
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Outbreak Detection Method for Influenza-Like Illness

Abstract: Epidemic outbreak detection is an important problem in public health and the development of reliable methods for outbreak detection remains an active research area. In this paper we introduce a Bayesian method to detect outbreaks of influenza-like illness from surveillance data. The rationale is that, during the early phase of the outbreak, surveillance data changes from autoregressive dynamics to a regime of exponential growth. Our method uses Bayesian model selection and Bayesian regression to identify the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Outbreaks of new (or old) diseases typically display an initial exponential rate of growth [14]. DUDE compares the set of cases in the monitor window with a baseline set of cases and generates an alarm if the presence of an unmodeled disease better explains the difference than simple variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of new (or old) diseases typically display an initial exponential rate of growth [14]. DUDE compares the set of cases in the monitor window with a baseline set of cases and generates an alarm if the presence of an unmodeled disease better explains the difference than simple variation.…”
Section: Discussionmentioning
confidence: 99%
“…A distinctive feature of an infectious outbreak is an initial period of exponential growth. [14] describes a Bayesian system, based on moving windows of ILI records, to detect a period of exponential growth that can signal the start of an outbreak. That system uses Bayes' factors to determine when it is likely that an outbreak has started.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no other study has been conducted on the performance of BODA. However, other algorithms using the Bayesian framework were used to detect outbreaks in various studies, most of which showed good performance (Garcia, Christen, & Capistran, 2015; Liao, Xu, Wang, & Liu, 2017; Texier et al., 2016, 2019). The BODA model has two advantages over traditional models, one using the Bayesian framework, which also uses the prior distribution to calculate the alarm threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper q = 0.4 is used to get 90% Confidence Interval by Equation 7• Model 4: Growth Value The fourth model is using RI growth value as a measurement to identify abrupt growing RIs. The anomaly label using growth value is given in Equation (8). It means the labeled weeks have RI growth value exceeding the median of the positive growth values.…”
Section: • Model 1: Simple Thresholdmentioning
confidence: 99%
“…In 2015, García YE utilized Bayesian model selection and Bayesian regression to detect outbreaks for ILI using surveillance data 8 . The method was applied to both the Spanish influenza outbreaks in USA San Francisco in 1918 and the acute respiratory illnesses (ARI) from Mexico San Luis Potosí for validation.…”
Section: Introductionmentioning
confidence: 99%